Borderland Lives in Northern South Asia - Schendel, Willem van.; Gellner, David N.; Project Muse. (Durham : Duke University Press, 2013)
This book provides valuable new ethnographic insights into life along some of the most contentious borders in the world. The collected essays portray existence at different points across India's northern frontiers and, in one instance, along borders within India. Whether discussing Shi'i Muslims striving to be patriotic Indians in the Kashmiri district of Kargil or Bangladeshis living uneasily in an enclave surrounded by Indian territory, the contributors show that state borders in Northern South Asia are complex sites of contestation. India's borders with Bangladesh, Bhutan, Burma/Myanmar, China, and Nepal encompass radically different ways of life, a whole spectrum of relationships to the state, and many struggles with urgent identity issues. Taken together, the essays show how, by looking at state-making in diverse, border-related contexts, it is possible to comprehend Northern South Asia's various nation-state projects without relapsing into conventional nationalist accounts.
Introduction: Northern South Asia's diverse borders, from Kachchh to Mizoram / David N. Gellner -- Borders without borderlands : on the social reproduction of state demarcation in Rajasthan / Anastasia Piliavsky -- Allegiance and alienation : border dynamics in Kargil / Radhika Gupta -- Naturalizing the Himalaya-as-border in Uttarakhand / Nayanika Mathur -- On the way to India : Nepali rituals of border crossing / Sondra L. Hausner and Jeevan R. Sharma -- The perils of being a borderland people : on the Lhotshampas of Bhutan / Rosalind Evans -- Developing the border : state and the political economy of development in Arunachal Pradesh / Deepak K. Mishra -- The micropolitics of borders : the issue of Greater Nagaland (or Nagalim) / Vibha Joshi -- Nodes of control in a South(east) Asian borderland / Nicholas Farrelly -- Histories of belonging(s) : narrating territory, possession, and dispossession at the India-Bangladesh border / Jason Cons -- Geographies and identities : subaltern partition stories along Bengal's southern frontier / Annu Jalais -- Afterword: Making the most of "sensitive" borders / Willem van Schendel.
English.
Description based on print version record.
Keywords: South Asia; South Asia -- Social conditions; South Asia -- Relations; South Asia -- Politics and government; South Asia -- Boundaries -- History; Social conditions; Politics and government; International relations; Boundaries; Regional and national history; Humanities; History; Asian history; History; Electronic books